Analyzing predictive approaches in martial arts research - Tropin, Y.; Podrigalo, L.; Boychenko, N.; Podrihalo, O.; Volodchenko, O.; Volskyi, D.; Roztorhui, M. (Pedagogy of Physical Culture and Sports, 2023)
Background and Study Aim Predicting the results of martial arts competitions is an important task that attracts the attention of both sports analysts and fans of these sports. The objective of this study is to perform an analytical examination of publications on martial arts prediction, with the aim of identifying the primary research directions in this field.